PERANCANGAN ULANG TATA LETAK FASILITAS DENGAN MENGGUNAKAN METODE KONVENSIONAL BERBASIS 5S: Array - Utari, Panca Wahyu; Hasibuan, Yetti Meuthia; Nasution, Rini Halila (JiTEKH, 2020)
The facility layout design greatly affects the performance of a company. Poor facility layout will lead to poor material flow patterns and relatively high movement of materials, products, information, equipment and labor which causes delays in product completion and increases production costs. Facility layout design aims to analyze improvements in production activities. In preparing the layout of the facility, this research applies the 5S method to see what needs to be improved and to redesign the factory layout. The object of this research was conducted at PT. XYZ. The results showed that the redesign of the facility layout of the light bulb processing factory of PT.XYZ consists of several parts that must be improved in order to obtain the best final layout. The redesign of this facility layout does not have to require additional areas, this can be done by rearranging it. Based on the trial questionnaire before applyingthe 5S method,it was found that seiri,seiso,seiton,seiketsu,shitsuke needed improvement, while after redesigning using 5S method, it was found that only seiketsu and shitsuke needed improvement.